Validation of a short measure of effort-reward imbalance in the workplace: evidence from China - Li, Jian; Loerbroks, Adrian (Journal of occupational health, 2012)
Japan's largest platform for academic e-journals: J-STAGE is a full text database for reviewed academic papers published by Japanese societies
Gesehen am 29.10.2018